2011
DOI: 10.1007/s12012-011-9109-z
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II Infusion–Induced Inflammation, Monocytic Fibroblast Precursor Infiltration, and Cardiac Fibrosis are Pressure Dependent

Abstract: The activated renin-angiotensin-aldosterone system increases blood pressure and intracellular signals, thus leading to cardiac fibrosis. Whether increased blood pressure or angiotensin II-activated signaling is responsible for elevated angiotensin II-induced cardiac remodeling is unknown. Here, we aimed to determine whether lowering blood pressure with hydralazine might prevent inflammation and cardiac fibrosis in response to angiotensin II. We used the C57/BL6 mouse model of angiotensin II infusion (1,500 ng/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
55
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 50 publications
3
55
0
Order By: Relevance
“…At the same time, our results on blood pressure complement the findings of Marvar and colleagues who used a similar approach with hydralazine to demonstrate that the pressor effects of Ang II are critical for the activation of circulating T lymphocytes and the expression of vascular inflammation in mice [31]. Interestingly, there is also evidence that hydralazine attenuates cardiac fibrosis and inflammation induced by pressive Ang II in mice, suggesting that blood pressure is also a key contributor to the expression of inflammation in other end organs affected by hypertension besides the brain [38].…”
Section: Discussionsupporting
confidence: 76%
“…At the same time, our results on blood pressure complement the findings of Marvar and colleagues who used a similar approach with hydralazine to demonstrate that the pressor effects of Ang II are critical for the activation of circulating T lymphocytes and the expression of vascular inflammation in mice [31]. Interestingly, there is also evidence that hydralazine attenuates cardiac fibrosis and inflammation induced by pressive Ang II in mice, suggesting that blood pressure is also a key contributor to the expression of inflammation in other end organs affected by hypertension besides the brain [38].…”
Section: Discussionsupporting
confidence: 76%
“…Hydralazine was chosen based on its antihypertensive properties of lowering blood pressure in a dose-dependent manner without acting on AngII receptors. 24,25 RAS upregulation was demonstrated in the animals that received AngII+hydralazine, as evidenced by a significant elevation in serum aldosterone, which is a downstream mediator and marker of RAS activation. Our primary observation using this model was that the addition of hydralazine to AngII resulted in normalization of the blood pressure and inhibition of the fibrosis that is normally seen in animals receiving AngII.…”
Section: Discussionmentioning
confidence: 97%
“…Our findings are in keeping with other studies that have suggested that the effects of AngII on fibrosis are blood pressure dependent. 24,25,39 Some reports have even suggested that blood pressure can affect the migration of fibrocytes (CD45 + /SMA + ) into the myocardium, but these reports did not elucidate a definitive mechanism. 25 In contrast, transgenic mice that overexpress the AT1a receptor and develop hypertrophy and fibrosis do so without developing hypertension, emphasizing the multifactorial pathways capable of promoting extracellular matrix deposition and fibrosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Angiotensin II acts through two receptors -AT1 and AT2, with AT1 activation playing a major role in the production of ECM proteins and vascular fibrosis 2,[95][96][97][98] . Whilst the precise mechanisms involved in angiotensin II related vascular fibrosis remain to be fully defined, increased activity of TGF-β-1, galectin-3, p38 MAPK and MMPs/TIMPs may all contribute.…”
Section: Angiotensin II Aldosterone and Endothelin-1mentioning
confidence: 99%